2015
DOI: 10.1088/0031-9155/60/18/7339
|View full text |Cite
|
Sign up to set email alerts
|

The electric field distribution in the brain during TTFields therapy and its dependence on tissue dielectric properties and anatomy: a computational study

Abstract: Tumor Treating Fields (TTFields) are a non-invasive, anti-mitotic and approved treatment for recurrent glioblastoma multiforme (GBM) patients. In vitro studies have shown that inhibition of cell division in glioma is achieved when the applied alternating electric field has a frequency in the range of 200 kHz and an amplitude of 1 - 3 V/cm. Our aim is to calculate the electric field distribution in the brain during TTFields therapy and to investigate the dependence of these predictions on the heterogeneous, ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
126
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(132 citation statements)
references
References 51 publications
(82 reference statements)
4
126
0
Order By: Relevance
“…There are two physical phenomena which underlie the effect of TTFields: dielectrophoresis which occurs mainly during cytokinesis, and dipole alignment. Electric field simulations have demonstrated that the frequencies expected to cause maximal dielectrophoretic forces during cytokinesis are within the range of 100-200 kHz, while the maximal effect on dipole alignment is expected to appear at higher frequencies (towards 1 MHz) [30]. It is therefore possible that the biphasic nature of the observed response is the outcome of dielectrophoresis induced at 200 KHz, and dipole alignment occurring at higher frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…There are two physical phenomena which underlie the effect of TTFields: dielectrophoresis which occurs mainly during cytokinesis, and dipole alignment. Electric field simulations have demonstrated that the frequencies expected to cause maximal dielectrophoretic forces during cytokinesis are within the range of 100-200 kHz, while the maximal effect on dipole alignment is expected to appear at higher frequencies (towards 1 MHz) [30]. It is therefore possible that the biphasic nature of the observed response is the outcome of dielectrophoresis induced at 200 KHz, and dipole alignment occurring at higher frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…TTFields are nonuniformly distributed within the treated region based on multiple parameters, which include the geometry of the treated organ, the distance between transducer arrays applied to the patient's skin, and the tissue's dielectric properties (20)(21)(22). The fields do not attenuate in correlation to the distance from the array, and may therefore be used for the treatment of deeply located tumors (21,22).…”
Section: Biophysics Of Ttfieldsmentioning
confidence: 99%
“…The fields do not attenuate in correlation to the distance from the array, and may therefore be used for the treatment of deeply located tumors (21,22). As electric fields do not have a half-life time, TTFields are continuously delivered during the course of treatment.…”
Section: Biophysics Of Ttfieldsmentioning
confidence: 99%
“…Electric field distribution within the brain is nonuniform, and is a function of the direction of a field, individual dielectric properties of adjacent tissue structures, and the orientation of the interfaces between them [9, 10]. The algorithm will compute the optimal paired configuration of transducer arrays that should be applied directly to a patient’s shaved scalp that will locally deliver the highest intensity of TTFields at the site of a tumor.…”
Section: Discussionmentioning
confidence: 99%
“…In general, high energy gamma radiation has a frequency in the order of exahertz (10 20 ), with a wavelength of picometers (10 −19 ), less than the diameter of an atom [8]. As the frequency of TTFields is much lower at 200 kHz, and the wavelength much longer (~1 mile), TTFields cannot be precisely focused and delivered to discrete regions of the brain in the same focal manner as RT [9, 10]. Treatment can, however, be optimized to ensure that field intensity is maximal at the site of a tumor [1113], a process which involves planning with the NovoTAL System software.…”
Section: Introductionmentioning
confidence: 99%